Kelimpahan dan komposisi sampah plastik di DAS Baturusa Provinsi Kepulauan Bangka Belitung - Riskiana, Refa; Effendi, Hefni; Wardiatno, Yusli (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2020)
The usage of plastic has been increasing from year to year for its durable, lightweight, sturdy, easy to form, and low cost production, so that plastic becomes a popular material. Plastics have affinities with persistent organic pollutant such as PCB, DDT, PAH and phthalates that can damage the ecosystem as well as harm to human. In this study plastic wastes were collected using nets in seven stations along Baturusa watershed, sorted based on its composing resin (RIC), then measured the abundance and the density rate on each station. 36% of the collected plastic wastes are Polypropylene (02), and 24% are LDPE (04). The highest density rate of collected plastic wastes was found on Mabet river (1.36 x 102 items/m3), followed by Baturusa river, and Rangkui river estuary. These three stations are located near the settlements so that the source of the plastic wastes comes from domestic activities. The variety of waste management showed a significant impact to the amount of plastic wastes on waters. One of the plastic waste management for the settlements is to carry out 3R (reduce, reuse, recycle), such as waste bank programs and implement EPR (extended producer responsibility) programme. The successfulness of this programme can only be achieved by the active participation of the waste bank customers and the implementation of 3R principle in daily life.